COVID-19, the COVID-19 response, and racial injustice: Associations with depressive and anxiety symptoms among US adults from April 2020 to March 2021 - Christopher G. Kemp; Augustina Mensa-Kwao; Tessa Concepcion; Matt Hughsam; Emily Queen; Moitreyee Sinha; Pamela Y. Collins (Elsevier, 2023)
Background: People in the United States have faced numerous large and intersecting threats to their mental health since the onset of the coronavirus disease pandemic. This study aimed to understand the unique relationships between these co-occurring threats - including the police killings of unarmed Black people and the fight for racial justice - and how they affect mental health symptoms among various demographic groups. Methods: Data on population mental health, state-level COVID-19 incidence rates, cases of police-involved killings, and occurrences of racial justice protests were analyzed. The primary outcome was depression or anxiety symptoms. Regression models were used to estimate prospective associations between individual-, household-, and state-level exposures to hypothesized mental health threats and subsequent depression or anxiety symptoms. Results: Data from 2,085,041 individual participants were included. Most were women (51.2%), and most were white, non-Hispanic (61.2%), with almost half (47.7%) reporting some loss of household income since March 13, 2020. Neither the killing of unarmed Black people by police, nor the above-average occurrence of Black Lives Matter (BLM) protests, were observed to be associated with anxiety or depressive symptoms in the overall population, though the BLM protests were associated with reduced depressive and anxiety symptoms among younger participants. State-level COVID-19 incidence risk was more strongly associated with depressive and anxiety symptoms among women, Black people, older people, and higher income people, compared to men, white people, younger people, and lower income people. Conclusion: Our findings are relevant for anticipating and addressing the mental health consequences of social injustice and protest movements in the context of COVID-19 pandemic, as well as future pandemics. Promoting population mental health requires addressing underlying social and structural inequities and prioritizing the pursuit of social justice and health equity as a primary mental health intervention.